Sexual dimorphism in the late Miocene mihirung Dromornis stirtoni (Aves: Dromornithidae) from the Alcoota Local Fauna of central Australia. Issue 5 (2nd September 2016) - Handley, Warren D.; Chinsamy, Anusuya; Yates, Adam M.; Worthy, Trevor H.
ABSTRACT: The dromornithids were giant flightless birds endemic to Australia from the late Paleogene to the late Pleistocene. Dromornithids are generally considered to be divergent members of the Anseriformes, but they display many convergent features with extant ratites. In this study, we investigate Dromornis stirtoni from the Alcoota Local Fauna, a species for which little is known of its biology. We used traditional methods of comparative morphology, mass estimation, landmark-based morphometrics, and histological investigations to determine the presence of medullary bone, to assess the possible presence, form, and extent of sexual dimorphism in D. stirtoni . Two morphological groups were identified for each main leg element, differing primarily in relative robustness. Core samples from femora and tibiotarsi shafts revealed medullary bone in the less robust morph, indicating that these were females. Mass, as estimated by algorithms applied to our preferred measurement of least-shaft circumference of tibiotarsi, was significantly different between males (mean = 528 kg) and females (mean = 451 kg). Therefore, male D. stirtoni were more robust but not much taller than the females and challenge the elephant bird, Aepyornis maximus, for the title of the most massive bird to have existed. Sexual dimorphism in this largest of all dromornithids, therefore, was like that of extant Anseriformes. We infer long-term monogamy, mutual display, shared parental care, female incubation, and aggressive defense of nests in these birds. The techniques of geometric morphometrics applied in this study maximize the use of fragmentary material, helping to overcome the common paleontological challenge of limited sample sizes. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Handley, W. D., A. Chinsamy, A. M. Yates, and T. H. Worthy. 2016. Sexual dimorphism in the late Miocene mihirung Dromornis stirtoni (Aves: Dromornithidae) from the Alcoota Local Fauna of central Australia. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1180298.